A multi agent system for monitoring industrial gas turbine start-up sequences. - Mangina, E.E (IEEE Transactions on power systems)
This paper introduces a novel technique for the condition monitoring of gas turbine start up sequences. The vast amount of data and the complex processes behind online fault detection indicate the need for an automated solution. A multi agent system that views the problem as the interaction of simple independent software entities, for effective use of the available data, is presented. The overall solution is derived from the combination of partial solutions provided by the components of the multi-agent system. As a consequence, data interpretation is achieved by converting the data into appropriate information and combining individual agents' information, resulting in an automatic fault diagnosis for the engineers. This multi-agent system can employ various intelligent system techniques and has been implemented using the ZEUS Agent building Toolkit